PMA Induction to Prostate Cancer Cell Lines: DU145 and LNCAP - Gonen, Ceren (British Journal of Healthcare and Medical Research, 2024)
Prostate cancer is the most commonly diagnosed cancer and the second leading cause of cancer mortality in men in the Western World. The effects of androgens are mediated by the Androgen Receptor (AR). Therefore, studies focus on the identification of AR-regulated genes that are also highly expressed in the prostate. STAMP family genes STAMP1/STEAP2 and STAMP2/STEAP4 have only expressed in androgen receptor-positive cells, the role of AR in STAMP family gene expression is an important question Phorbol 12-myristate 13-acetate, NF-κB Activator, PMA, TPA PMA is used at 100nM final concentration after transfection of Hismax vector and Hismax STAMP1 to DU145-brain metastases of prostate cancer cell line. DU145 cell line kinetics were shown. PMA induction to LNCaP cells.was done. In summary, the data presented show that STAMP1 is involved in a signaling pathway that is linked to cell cycle progression as well as inhibition of apoptosis. Consistent with its increased expression in prostate cancer, these data suggest that STAMP1 may play important roles in prostate cancer development and progression